Pengaruh Pengetahuan, Kepercayaan, dan Kualitas Layanan Terhadap Preferensi Menabung Pada Perbankan Syariah Dengan Promosi Sebagai Variabel Moderasi (Studi Pada Pedagang Pasar Km 5 Kota Palembang) - Ardikha, Ninda Ferda; Siska, Emi Yulia; Aryanti, Aryanti (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to analyze the influence of knowledge, trust, and service quality on savings preferences in Islamic banking with promotion as a moderating variable. The study was conducted on traders at KM 5 Market in Palembang City using quantitative methods. Primary data were obtained through questionnaires distributed to 198 respondents using a purposive sampling technique. Data analysis used Partial Least Square (PLS) through SmartPLS 4. The results showed that knowledge and trust variables had a negative effect on savings preferences, while service quality had a positive and significant effect on savings preferences. In addition, the results of moderation showed that promotion could not strengthen the influence between knowledge and savings preferences, promotion variables weakened the influence between trust and savings preferences, and promotion could further strengthen the influence between service quality and savings preferences.